Biopesticides and bioagents : novel tools for pest management - Anwer, Md. Arshad (Waretown, NJ : Apple Academic Press, 2017)
"Insects, diseases, and weeds cause an almost 30% yield loss per annum in agricultural production, resulting in an increased consumption of pesticides by 20% per annum throughout the world. This comprehensive volume looks at the status of biopesticides and biocontrol agents in agriculture. It will be a critically important reference work, providing basic facts and studies on new and current discoveries of the role of biopesticides and bioagents in integrated pest management (IPM). The book contains four main sections, covering the status of biopesticides and biocontrol agents in agriculture, plant health-promoting biocontrol agents, parasitoids and predators, genetically modified crops and Bacillus thuringiensis, and phytochemicals in biocontrol. The volume provides information regarding new advances in microbial, biochemical, and genetically modified and organic nanoparticles in integrated pest management. Biopesticides and Bioagents: Novel Tools for Pest Management should find a prominent place on the shelves of agriculture and plant scientists, microbiologists, biotechnologists, plant pathologists and entomologists working in academic and commercial agrichemical situations, and in the libraries of all research establishments and companies where this exciting subject is researched, studied, or taught. "--Provided by publisher.
chapter 1 Status Of Biopesticides And Biocontrol Agents In Agriculture: An Overview -- part Part I: Plant Health Promoting Biocontrol Agents -- chapter 2 Trichoderma$1 (Ban Impeccable Plant Health Booster /s Najam Waris Zaidi -- chapter 3 Aspergillus Niger: A Phosphate Solubilizing Fungus As Biocontrol Agent -- chapter 4 Flourescent Pseudomonads: A Potential Bio-control Agents Against Plant Diseases -- part Part II: Entomopathogens -- chapter 5 Entomopathogenic Fungi: Introduction, History, Classification, Infection Mechanism, Enzymes, And Toxins / Waheed Anwar -- chapter 6 Entomopathogens And Their Mass Production And Application / Kalmesh Managanvi -- chapter 7 Entomopathogenic Nematodes: An Emerging Biocontrol Agent For Insect Pests Management -- chapter 8 Role Of Insect Viruses In The Management Of Insect Pests / Chandra Shekhar Prabhakar -- part Part III: Parasitoids and Predators -- chapter 9 Trichogramma: An Egg Parasitoid In Insect Pest Management / Tarak Nath Goswami, Anil, Tarak Brambha Maji, Pranab Barma, and -- chapter 10 Coccinellids In Insect Pest Management: Problems And Prospects / Pranab Barma -- chapter 11 Chrysopid: A Potential Biocontrol Agent / Nithya Chandran -- part Part IV Genetically Modified Crops, Bacillus Thuringiensis And Phytochemicals In Bioconrol -- chapter 12 Genetically Modified Crops For Insect Pests And Disease Resistance -- chapter 13 Bacillus Thuringiensis And Insect Pest Management / Anil, Lokender Kashyap, Tarak Nath Goswami, Vikas Kumar Patel, and -- chapter 14 Role Of Phytochemicals In Insect Pest Management / Tamoghna Saha.
Keywords: Natural pesticides; Biological pest control agents; Phytopathogenic microorganisms -- Control; Weeds -- Control